Acquisition Behavior of Emerging Versus Developed Market Multinationals - Ahmed, Kashif; Bebenroth, Ralf (Organizations and Markets in Emerging Economies, 2019)
The purpose of this paper is to investigate how emerging and developed market multinationals (EMMs and DMMs) differ in their acquisition behavior (vis-à-vis the choice of partial versus full acquisitions) when entering a developed market economy, Japan. We hypothesize that EMMs prefer partial acquisitions, whereas DMMs prefer full acquisitions due to what we call the country-of-origin effect. Additionally, we hypothesize that this country-of-origin effect is more pronounced for smaller firms. The results, based upon 224 strategic cross-border acquisitions in Japan, support these two hypotheses. This study contributes to the literature on EMMs.
Keywords: Emerging markets multinationals (EMMs); developed market multinationals (DMMs); partial acquisitions; full acquisitions; Japan